(untitled) (Perner’s Contacts, 2019)
In recent years, climate change has had a significant impact on inland waterways of international importance. The main problem affecting the continuity of navigation is the fluctuation of water level. The problem is not only low but also high water levels. Both extremes result in navigation restrictions, resulting in reduced reliability of water transport. One of the ways to increase reliability is also to optimize the shape of the hull of vessels. This concerns the optimization of the vessel’s hull for navigation on waterways with a low water level. Restricted navigational draft significantly limits navigation especially in summer. Hull shape optimization is a process that consists of several steps at the end of which it is possible to compare the optimized hull shape to the original one. The optimization process depends on the correct definition of the input elements. CFD analysis is most often used for optimization. The principle is to create a computational domain that consists of a real geometric model and a discretized shape, a definition of boundary conditions, a set of physical properties, and appropriate computational methods.